The Effect of Emotional Intelligence and Self Effycacy Towards Students Achievement - Farhan, Muhamad; Alfin, Edward (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2019)
This research aims at revealing the effect of emotional intelligence and self-efficacy towards learning achievement of the 8th grade students in SMP Islam Terpadu Ar-Rahman south of Jakarta. This type of research is a survey method. Data instruments are emotional intelligence questionnaires and self-efficacy questionnaires, the mathematics learning achievement data from the daily test scores of students through the description questions. The data analysis technique used is multiple regression analysis. The results of the regression analysis of significance between emotional intelligence on mathematics learning achievement showed the results as much as 0,551 (0,551 > 0,05), self-efficacy towards mathematics learning achievement as much as 0.333 (0.333> 0.05). The significance of variance analysis was obtained at 0.350 (0.350> 0.05). The results of this data analysis show that emotional intelligence and self-efficacy together no meaningful affect the learning achievement of mathematics. The implication of this study is that students who have high and moderate emotional intelligence and self-efficacy do not have a significant effect on improving learning achievement, thus emotional intelligence and self-efficacy are not the main factors that influence student learning achievement.